1995
DOI: 10.1161/01.atv.15.8.1172
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload Augments the Development of Atherosclerotic Lesions in Rabbits

Abstract: Iron, a major oxidant in vivo, could be involved in atherosclerosis through the induction of the formation of oxidized LDL, a major atherogenic factor. This study was designed to test this hypothesis experimentally. Four groups of New Zealand White rabbits were included: iron-overloaded/hypercholesterolemic (group A, n = 8), iron-overloaded (group B, n = 6), hypercholesterolemic (group C, n = 6), and untreated (group D, n = 6). Iron overload was achieved by the intramuscular administration of 1.5 g of iron dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(87 citation statements)
references
References 49 publications
4
81
0
2
Order By: Relevance
“…However, it seems likely that increased ferritin reflects both the involvement of inflammation, as CRP does, and independent actions of excess iron. It is known that increased accumulation of iron affects insulin synthesis and secretion in the pancreas (Wilson et al, 2003) and interferes with the insulin-extracting capacity of the liver (Niederau et al, 1984), thereby leading to peripheral hyperinsulinaemia and impaired insulin secretion; that deposition of iron in muscle reduces glucose uptake because of muscle damage; (Merkel et al, 1988) and that iron accelerates atherosclerosis and damages endothelium in experimental models (Araujo et al, 1995;Lekakis et al, 1999) (catalytic iron converts relatively unreactive radical species such as H 2 O 2 into highly reactive species such as hydroxyl radical, and thereby favours oxidative attack on cell membranes and other cell components) (Oberley, 1988;Wolff, 1993;Andrews, 1999;Beard, 2001). Since insulin in turn stimulates cellular iron uptake by increasing the externalization of transferrin receptor, and may also stimulate the production of erythropoietin (Davis et al, 1986), a vicious circle leading to insulin resistance and diabetes may set in.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems likely that increased ferritin reflects both the involvement of inflammation, as CRP does, and independent actions of excess iron. It is known that increased accumulation of iron affects insulin synthesis and secretion in the pancreas (Wilson et al, 2003) and interferes with the insulin-extracting capacity of the liver (Niederau et al, 1984), thereby leading to peripheral hyperinsulinaemia and impaired insulin secretion; that deposition of iron in muscle reduces glucose uptake because of muscle damage; (Merkel et al, 1988) and that iron accelerates atherosclerosis and damages endothelium in experimental models (Araujo et al, 1995;Lekakis et al, 1999) (catalytic iron converts relatively unreactive radical species such as H 2 O 2 into highly reactive species such as hydroxyl radical, and thereby favours oxidative attack on cell membranes and other cell components) (Oberley, 1988;Wolff, 1993;Andrews, 1999;Beard, 2001). Since insulin in turn stimulates cellular iron uptake by increasing the externalization of transferrin receptor, and may also stimulate the production of erythropoietin (Davis et al, 1986), a vicious circle leading to insulin resistance and diabetes may set in.…”
Section: Discussionmentioning
confidence: 99%
“…Since Sullivan (1) raised the hypothesis that iron overload could be a risk factor for CAD, many investigators have tested this possibility, but no definitive conclusion has been reached due to conflicting results (3,4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(23)(24)(25). Since the occurrence of HFE gene mutations associated with HH provides a valuable opportunity to test indirectly whether iron overload plays a role in atherosclerosis, the prevalence of these two mutations in patients with coronary atherothrombosis and in healthy controls was determined in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with the demonstration that iron catalyzes the synthesis of oxygen-reactive products (2), it has been also proposed that iron could play a role in LDL lipid peroxidation (3,4), an early step in atherogenesis (5). To support this hypothesis, it has been experimentally observed that iron overload contributes to atherogenesis in rabbits (6); however, other investigators demonstrated that, in the same animal model, iron overload causes a decrease in plasma cholesterol levels as well as in the formation of lesions in the aortic arch (7). Similarly, whereas some epidemiological studies (8)(9)(10)(11) have found a positive association between CAD and clinical markers of iron overload, other reports have found either a negative association (12) or none at all (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Thiobarbituric Acid-Reactive Substance (TBARS) assay of aortic homogenates [21]: 20 μL aortic homogenate was added to 2 mL 40 mmol/L H 2 SO 4 (Merck), then 0.25 mL 10% wt/vol phosphotungstic acid (Sigma Chemical Co) was added and mixed. The mixture was centrifuged at 3000 rpm for 10 minutes, the supernatant was discarded, and the sediment was mixed with 1 mL 40 mmol/L H 2 SO 4 and 0.15 mL 10% wt/vol phosphotungstic acid.…”
Section: Determination Of Glutathione Peroxidase [Gpx] Enzymementioning
confidence: 99%